“You would not be in a hurry to go back home”: patients’ willingness to participate in HIV/AIDS clinical trials at a clinical and research facility in Kampala, Uganda - Sebatta, Deborah Ekusai; Siu, Godfrey; Nabeta, Henry W.; Anguzu, Godwin; Walimbwa, Stephen; Lamorde, Mohammed; Bukenya, Badru; Kambugu, Andrew (BMC Medical Ethics, 2020)
Few studies have examined factors associated with willingness of people living with HIV (PLHIV) to participate in HIV treatment clinical trials in Sub-Saharan Africa. We assessed the factors associated with participation of PLHIV in HIV treatment clinical trials research at a large urban clinical and research facility in Uganda. A mixed methods study was conducted at the Infectious Diseases Institute (IDI), adult HIV clinic between July 2016 and January 2017. Data were collected using structured questionnaires, focused group discussions with respondents categorised as either participated or never participated in clinical trials and key informant interviews with IDI staff. A generalized linear model with a logit link function was used for multivariate analyses while the qualitative data were summarized using a thematic approach. We enrolled a total of 202 and analysed 151 participants, 77 (51%) of whom were male with mean age of 41 years. The majority 127 (84%) expressed willingness to participate in treatment clinical trials if given an opportunity. At bivariate analysis, willingness to participate was significantly associated with respondents’ perception of a satisfactory compensation package (P-value < 0.002, 0.08–0.56), special status accorded (P-value < 0.001, 0.05–0.39) and belief that their health status would improve (P-value< 0.08, 0.03–0.58) while on the clinical trial. At multivariate analysis, a satisfactory compensation package (P-value< 0.030, 0.08–0.88) and special status accorded in clinical trials (P-value< 0.041, 0.01–0.91) remained significant. The qualitative data analysis confirmed these findings as participants valued the privilege of jumping the clinic waiting queues and spending less time in clinic, the wide range of free tests offered to trial participants, unrestricted access to senior physicians and regular communication from study team. Additionally, free meals offered during clinic visits meant that participants were not in a hurry to go back home. Barriers to participation included the perception that new drugs were being tested on them, fear of side effects like treatment failure and the uncertainty about privacy of their data. We found overwhelming willingness to participate in HIV treatment clinical trials. This was largely extrinsically influenced by the perceived material and health-related benefits. Investigators should pay attention to participants’ concerns for benefits which may override the need to understand study procedures and risks.
Keywords: Barriers; Clinical trials; Compensation; Willingness to participate; Perceived benefit